2017
DOI: 10.1371/journal.pone.0179302
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and drivers of global mangrove forest change, 1996–2010

Abstract: For the period 1996-2010, we provide the first indication of the drivers behind mangrove land cover and land use change across the (pan-)tropics using time-series Japanese Earth Resources Satellite (JERS-1) Synthetic Aperture Radar (SAR) and Advanced Land Observing Satellite (ALOS) Phased Array-type L-band SAR (PALSAR) data. Multi-temporal radar mosaics were manually interpreted for evidence of loss and gain in forest extent and its associated driver. Mangrove loss as a consequence of human activities was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
323
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(341 citation statements)
references
References 38 publications
4
323
0
14
Order By: Relevance
“…The scale of mangrove conversion to aquaculture has been historically dramatic, with an estimated 140,000 ha of mangrove lost to conversion in the 1950s-1980s (Primavera, 2000). A global-scale quantitative assessment of the proximate drivers of mangrove deforestation has only recently been produced (Thomas et al, 2017), and a qualitative survey of 10 mangrove experts by UNEP (2014) suggested that aquaculture is still one of the largest threats to mangroves globally, though other drivers such as overexploitation, pollution and coastal development are also important. All drivers are expected to increase in magnitude in the future (UNEP, 2014).…”
Section: Mangrove Losses Due To Deforestationmentioning
confidence: 99%
“…The scale of mangrove conversion to aquaculture has been historically dramatic, with an estimated 140,000 ha of mangrove lost to conversion in the 1950s-1980s (Primavera, 2000). A global-scale quantitative assessment of the proximate drivers of mangrove deforestation has only recently been produced (Thomas et al, 2017), and a qualitative survey of 10 mangrove experts by UNEP (2014) suggested that aquaculture is still one of the largest threats to mangroves globally, though other drivers such as overexploitation, pollution and coastal development are also important. All drivers are expected to increase in magnitude in the future (UNEP, 2014).…”
Section: Mangrove Losses Due To Deforestationmentioning
confidence: 99%
“…From these composites, Normalized Differenced Vegetation Index (Pettorelli, ), Normalized Difference Water Index (McFeeters, ) and several other index layers were generated for use as spectral predictors (Table ). The provision of spectral data for two time periods facilitates the estimation of change in land cover extent, which is important for monitoring the impact of threatening processes such as deforestation (Hansen et al., ), fragmentation (Haddad et al., ), coastal reclamation (Murray et al., ), aquaculture (Thomas et al., ) and water extraction (Tao et al., ). Future versions of Remap will allow users to choose any point in time between the launch of Landsat 5 and the present day to develop their classifications.…”
Section: Remap: Remote Ecosystem Monitoring and Assessment Pipelinementioning
confidence: 99%
“…In terms of carbon footprints, Kauffman and colleagues (2017) reported new estimates of greenhouse gas (GHG) emissions resulting from the conversion of mangrove forests into aquaculture ponds and concluded that 1603 kg of carbon dioxide equivalent (CO2e) is emitted for every kilogram of shrimp produced on lands formerly occupied by mangroves. Future predictions are even more warning as 156,480 km2 of mangroves would need to be converted into shrimp farms in the coming 9 years, an area larger than the current extent of existing mangrove forests worldwide (134,300 km2) (Thomas et al, 2017). Thus horizontal expansion of shrimp farming is not an option to increase production in future, rather intensification is.…”
Section: Shrimp Aquaculture: Genesis and Problemsmentioning
confidence: 99%